Peningkatan Aksesibilitas Informasi Wisata Melalui Media Digital dan Road Map Panduan di Desa Wisata Sawarna - Danu Sakhi Aksa Aksa; Deni Agung Ferdiansyah; Ilham Maulana; Julyan Rachman; Muhammad Aprizal Wijatmiko; Nova Amelia; Rayhan Dewanta Irwan Rutlan; Roni Setiyawanto; Syifa Annisa Annisa; Vicky Eka Syahputra; Zaky Abdullah Siraj; Joni Warta (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
Desa Wisata Sawarna, located in Bayah District, Lebak Regency, Banten Province, experiences increasing tourist visits; however, the availability of tourist information remains suboptimal. This Community Service Program (KKN) addresses this challenge through the implementation of two main infrastructure solutions: a digital running text display system and a comprehensive tourism area road map. The running text displays key information about tourist attractions at strategic locations near the beach entrance, while the road map provides comprehensive guidance covering main routes, accommodation points, and important facilities. The implementation process involved coordination with village officials and tourism managers, site surveying, LED module assembly and programming, and map design based on field data. The results demonstrate successful installation of both infrastructure elements, improved accessibility of public information for tourists, enhanced visibility of the tourism area identity, and easier navigation for visitors. This KKN initiative represents a practical example of how students can contribute to sustainable tourism development in Sawarna Tourism Village through the application of simple yet effective technological solutions.